Universal background checks for handgun purchases can reduce African American homicide rates - Kaufman, EJ; Morrison, CN; Olson, EJ; Humphreys, DK; Wiebe, DJ; Martin, ND; Sims, CA; Hoofnagle, MH; Schwab, CW; Reilly, PM; Seamon, MJ (Wolters Kluwer Health, 2020)
Background: Federal law requires background checks for firearms purchased from licensed dealers, but states can extend requirements to private sales of handguns and purchases at gun shows (universal background checks for handguns: UBC-HG). Although firearm homicide disproportionately affects African Americans, little is known about how UBG-HG impacts African Americans. We hypothesized that implementation of UBC-HG would reduce rates of firearm homicide of African Americans.